Cloning, sequencing, and identification using proteomic tools of a protease from bromelia hieronymi mez - Bruno, Mariela Anahí (2011)
Fruits of Bromelia hieronymi, a tropical South American plant, possess a high content of peptidases with potential biotechnological uses. Total RNA was extracted from unripe fruits and peptidase cDNA was obtained by 3′RACE-PCR. The consensus sequence of the cysteine peptidase cDNA contained 875 bp, the 690 first ones codifying for a hypothetical polypeptide chain of the mature peptidase, named Bh-CP1 (molecular mass 24.773 kDa, pI 8.6, extinction molar coefficient 58,705 M−1 cm−1). Bh-CP1 sequence shows a high percentage of identity with those of other cysteine plant proteases. The presence of highly preserved residues is observed, like those forming the catalytic site (Gln19, Cys25, His159, and Asn175, papain numbering), as well as other six Cys residues, involved in the formation of disulfide bounds. Molecular modeling results suggest the enzyme belongs to the α + β class of proteins, with two disulfide bridges (Cys23–Cys63 and Cys57–Cys96) in the α domain, while the β domain is stabilized by another disulfide bridge (Cys153–Cys203). Additionally, peptide mass fingerprints (PMFs) of the three peptidases previously isolated from B. hieronymi fruits (namely hieronymain I, II, and III) were performed and compared with the theoretical fingerprint of PMF of Bh-CP1, showing a partial matching between the in silico-translated protein and hieronymain II.